Gambaran Kualitas Hidup Anak Usia 6-18 Tahun yang Menjalani Kemoterapi di Rumah Sakit Kanker Dharmais, Jakarta Barat - MURDINI UMIATI; WINDY RAKHMAWATI; BANGUN SIMANGUNSONG (Indonesian Journal of Cancer)
Quality of life is defined as minimal presence of the adverse impact of treatment on the patients perceptions of his or her own functioning. This study is to describe the quality of life among children who received chemotherapy.